The Effects of Advertising Spending and Event Sponsorship on Brand Equity in the Ethiopian Brewery Industry (Global Journal of Management and Business Research, 2016)
The field of branding and brand equity is new area of research in Ethiopia. The study adapts an exploratory approach to measure the effects of advertising spending and event sponsorship effect on consumer-based brand equity because there is no study conducted in the Ethiopia beer market. Accordingly, the study assumes advertising spending and event sponsorships affecting brand equity dimensions positively. Hence, a conceptual model has been built and structural equation modeling (SEM) is used to verify the model. The brand equity dimensions (brand awareness, brand association, perceived quality and brand loyalty) are the dimensions the study was conceptualized and used to measure consumer-based brand equity. A quantitative research was undertaken and a cross-sectional descriptive survey research design in nature was applied in the study.The study confirmed that from advertising spending intensity: television advertising spending has a positive effect on brand awareness; and outdoor advertising has a positive effect on brand awareness, brand association, and perceived quality.
Keywords: marketing; advertising spending frequency; event sponsorship; brand equity dimensions; ethiopia